GCMS and LCMS/MS Based Analysis for the Identification and Characterization of Bioactive Metabolites of Seaweed Kappaphycus striatus as an Anti-hypertensive and Anti-hypercholesterolemic Agent - Mohsin, Hannis Fadzillah; Eshak, Zolkapli; Sultan, Sadia; Ahmad, Wasim; Amini, Mohammad Humayoon; Ashraf, Kamran (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Over 50% of the population in Malaysia has hypercholesterolemia, which puts them at a high risk of cardiovascular disease. Both food sources and the ingredients in traditional medications are essential to the treatment of this ailment. Seaweeds are naturally occurring dietary bioresources that have garnered a lot of attention recently. The local seaweed Kappaphycus striatus (K. striatus) contains numerous beneficial phytoconstituents that have the potential to serve as new drug candidates due to their health benefits. Thus, the aim of the study was to analyze and characterize the phytoconstituents present in the K. striatus. Materials and Methods: Extraction was carried out by a simple maceration method. The analysis of phytoconstituents was carried out via GCMS, HPLC, and LCMS methods. The GCMS chromatogram of the components were compared with the database of known components from the GC-MS NIST (2008) library, whereas the LCMS chromatographic profiles were analyzed based on the accurate mass data identified, and the predicted compounds were annotated using the METLIN database. Results: HPLC analysis profiling shows the presence of most of the polar phytoconstituents. LCMS and GCMS analysis results identified and characterize different types of bioactive compounds in the methanolic extract of K. striatus. Some of the compounds have been identified as potential anti-hypertensive and anti-hypercholesterolemia agents, as reported in previous studies. Conclusion: We conclude that the precise identification is crucial for understanding the potential pharmacological activities of these compounds. The effectiveness of K. striatus phytoconstituents in treating hypercholesterolemia requires additional validation through in vivo research. These discoveries highlight the potential of K. striatus as a significant source of therapeutic agents and lay the foundation for the development of novel medications for treatment of hypertension and hypercholesterolemia.
Keywords: Kappaphycus striatus; Seaweed; LCMS; GCMS; HPLC; Hypercholesterolemia